2020
DOI: 10.29313/jiff.v3i1.5118
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Indeks Aterogenik Plasma Log (TG/HDL) pada Wanita Obes dan Non Obes

Abstract: Obesitas saat ini telah menjadi masalah kesehatan di dunia karena merupakan salah satu faktor bagi timbulnya penyakit seperti dislipidemia, stroke, penyakit jantung koroner dan lain-lain. Salah satu prediktor yang spesifik untuk menilai risiko terjadinya Penyakit Jantung Koroner (PJK) adalah dengan mengukur Indeks Aterogenik Plasma (IAP). IAP dihitung dengan menggunakan rumus Log(TG/HDL). Penelitian ini bertujuan untuk mengetahui hubungan antara obesitas dengan profil High Density Lipoprotein (HDL), trigliseri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The atherogenic index value is one of the strongest markers of the risk of atherosclerosis and CHD compared to the results of the parameters of each lipid profile. Research by Niroumand et al (2015) and Kaniawati (2020) showed that the atherogenic Index of Plasma (AIP) was strongly associated with obesity (hip circumference and BMI) and physical activity (p<0,005). The atherogenic index value is not influenced by smoking habits, history of diabetes mellitus (DM), and hypertension (Edwards et al, 2017;K.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The atherogenic index value is one of the strongest markers of the risk of atherosclerosis and CHD compared to the results of the parameters of each lipid profile. Research by Niroumand et al (2015) and Kaniawati (2020) showed that the atherogenic Index of Plasma (AIP) was strongly associated with obesity (hip circumference and BMI) and physical activity (p<0,005). The atherogenic index value is not influenced by smoking habits, history of diabetes mellitus (DM), and hypertension (Edwards et al, 2017;K.…”
Section: Discussionmentioning
confidence: 98%
“…Niroumand et al (2015) in their research showed that plasma atherogenic index values had a significant correlation with abdominal circumference, BMI, and physical activity (p-value <0.05) on the incidence of CHD. The research by Kaniawati (2020) shows that there is a significant relationship between abdominal cirumference and LDL levels, triglycerides, and plasma atherogenic index (AIP).…”
Section: Discussionmentioning
confidence: 99%